OneCGIAR SKOSMOS sub-concept schema in AGROVOC - CGIAR Platform for Big Data in Agriculture (2021)
37 fully defined CGIAR concepts were submitted and integrated into aGROVOC, thus validating the workflow steps. Training was provided by FAO in the use of the curation tools. The concepts sub-schema is online in SKOMOS format, ready to receive submitted concepts and provide direct visualisation of CGIAR concepts, structured.